2018
DOI: 10.21873/anticanres.12431
|View full text |Cite
|
Sign up to set email alerts
|

MEKK3 Sustains EMT and Stemness in Pancreatic Cancer by Regulating YAP and TAZ Transcriptional Activity

Abstract: Abstract. Background Pancreatic cancer remains one of the most lethal and poorly understood human malignancies (1, 2). It has the lowest 5-year relative survival rate among solid tumors at 8% (3), and is projected to become the second leading cause of cancer-related death by 2030 in Western countries (4). Poor prognosis in pancreatic cancer is attributed to its early metastatic behavior, aggressive clinical course, and limited efficacy of chemotherapeutic treatments (5, 6).Epithelial-to-mesenchymal transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…MEKK3 is a serine/threonine kinase that can be activated by different signaling pathways. Previous studies showed that MEKK3 is essential for T-cell or cancer cell proliferation [46,47]. The similar defects induced by depletion of MEKK3 and WDR62 suggest that MEKK3, like WDR62, may control NPC proliferation and differentiation.…”
Section: Resultsmentioning
confidence: 82%
“…MEKK3 is a serine/threonine kinase that can be activated by different signaling pathways. Previous studies showed that MEKK3 is essential for T-cell or cancer cell proliferation [46,47]. The similar defects induced by depletion of MEKK3 and WDR62 suggest that MEKK3, like WDR62, may control NPC proliferation and differentiation.…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, YAP activity has been demonstrated to be influenced by several other stimuli known to impact on hepatocyte differentiation, such as hormonal signals acting through G-protein-coupled and tyrosine kinase receptors 32,33 , and to play a pivotal role in EMT 14 , a process responsible for hepatocyte dedifferentiation in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…YAP1 has been associated with stemness in cancer cells and its inhibition has been shown to interfere with growth of stem-like cells [54,55]. Here we conducted sphere formation assays to examine the effects of gemcitabine, visudyne or tivantinib as single agents or in combination with fendiline on self-renewal capacity [55].…”
Section: Resultsmentioning
confidence: 99%